(untitled) (Archives of Mechanics - Test, 2002)
Some mean value formulae and bounds on the thermal energy for the steady-state heat conduction problems are proven. The formulation is based on the analogy which exists between the linear elasticity and heat conduction. The formalism of the applied analogy follows the Wojnar’s approach. Some examples illustrate the applications of the theorems derived.